Crystal engineering of co‐crystal of nicotinic acid and pyrogallol: an experimental and theoretical electron density analysis. Issue 6 (29th November 2021) - Iqbal, Alia; Mehmood, Arshad; Noureen, Sajida; Lecomte, Claude; Ahmed, Maqsood
Abstract : Experimental and theoretical charge density analysis of a cocrystal of nicotinic acid and pyrogallol provides insight into the mechanism of nucleation and growth of the cocrystal. Abstract : Experimental electron density analysis by means of high‐resolution X‐ray diffraction data up to singθ/λmax = 1.11 Å −1 at 100 (1) K has been performed to analyze the detailed structure and the strength of intermolecular interactions responsible for the formation of a new solid form of nicotinic acid (NA), cocrystallized with pyrogallol (PY). There are two NA–PY units in the asymmetric unit. The experimental results are compared with the results obtained from theoretical structure factors modeled using periodic boundary DFT calculations. Both refinements were carried out using the Hansen and Coppens multipolar formalism (in MoPro program). The non‐centrosymmetric and polar nature of the crystal system rendered the multipolar refinement challenging which was addressed by involving the transferability principle. This study highlights the significance of the transferability principle in electron density modeling in non‐routine situations. The 2:2 cocrystal of NA–PY exhibits a zigzag, brickwall and sheet‐like layered structure in three dimensions and is stabilized by strong intra‐ and inter‐molecular hydrogen bonding through N—H…O and O—H…O bonds, some of them due to the zwitterion nature of NA as well as weak interactions between the PY molecules. Ranking these interactions via topological analysis of the electron density shows the leading role of the NA–NA substructure which drives the organization of the cocrystals. These strong interactions between the NA zwitterions may explain why Z ′ = 2.